2020
DOI: 10.1182/bloodadvances.2019001208
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells promote alloengraftment in a model of late-gestation in utero hematopoietic cell transplantation

Abstract: In utero hematopoietic cell transplantation (IUHCT) has the potential to cure congenital hematologic disorders including sickle cell disease. However, the window of opportunity for IUHCT closes with the acquisition of T-cell immunity, beginning at approximately 14 weeks gestation, posing significant technical challenges and excluding from treatment fetuses evaluated after the first trimester. Here we report that regulatory T cells can promote alloengraftment and preserve allograft tolerance after the acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…The upregulated Tregs and the high expression of anti‐inflammatory cytokines seen upon stimulation with donor cells in our study may have the effect of increasing the threshold for T cell activation 47 . This correlates with recently published data describing injection of host‐derived traditional Treg to promote allo‐engraftment in immunocompetent mice 50 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The upregulated Tregs and the high expression of anti‐inflammatory cytokines seen upon stimulation with donor cells in our study may have the effect of increasing the threshold for T cell activation 47 . This correlates with recently published data describing injection of host‐derived traditional Treg to promote allo‐engraftment in immunocompetent mice 50 …”
Section: Discussionsupporting
confidence: 88%
“…47 This correlates with recently published data describing injection of host-derived traditional Treg to promote allo-engraftment in immunocompetent mice. 50 Another putative mechanism is the generation of regulatory B cells (Breg) which have recently emerged as important mediators of transplant success. 51 Though we did not find evidence of a donor-specific antibody-mediated response, this does not exclude Breg responses acting via IL10 and TGFβ.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these studies, there are also preclinical studies investigating the method of in utero HCT for prevention of congenital hematological diseases, but the injection window and technical difficulties have not been overcome yet. Nevertheless, it was recently demonstrated that treatment with tolerance-inducing Tregs and Tr1 cells prevented GvHD and promoted long-term multilineage chimerism in mice receiving in utero HCT ( 82 ).…”
Section: Clinical Application Of Tr1 Cellsmentioning
confidence: 99%
“…In vivo imaging of BM has demonstrated that Tregs cluster proximal to hematopoietic stem cells (HSCs) and that adenosine generated by Tregs maintains HSC quiescence and can promote allo-HSC engraftment (14,15). Additionally, Tregs have been shown to play a critical role in improving graft versus host disease (GVHD) and recovery following BM transplantation (16)(17)(18). These observations indicate that Tregs are active regulators of homeostasis within the BM.…”
Section: Introductionmentioning
confidence: 99%